DIGITAL TRANSFORMATION IN HORTICULTURAL PRODUCT PROMOTION: THE EFFECTIVENESS OF SOCIAL MEDIA-BASED ADVERTISING STRATEGIES ON INCREASING SALES OF YOUNG FARMERS - Atik Sukmaningrum (CV. Radja Publika, 2025)
This study aims to analyze the effectiveness of social media-based advertising strategies in increasing sales of horticultural products managed by young farmers. The research approach uses quantitative methods with the support of qualitative data, through surveys of 60 young farmers and in-depth interviews to obtain comprehensive information on digital marketing strategies. The results show that the majority of young farmers aged 21–35 years use Instagram, Facebook, TikTok, and WhatsApp Business platforms as the main means of promotion. The most widely used advertising strategies include organic content (75%), paid advertising (60%), and partnerships with micro-influencers (30%). Data analysis shows that the combination of visual content and paid advertising has driven an average increase in sales of 35% in the past six months, much higher than farmers who still rely on traditional promotions with a 10–15% increase. These findings support the theory of content marketing, AIDA, and digital marketing performance, which assert that social media-based promotions can increase consumer engagement, build product branding, and expand market reach. This study recommends optimizing digital strategies and strengthening online marketing literacy to support the sustainability of young farmers' horticultural businesses in the digital economy era.